Field-Deployable Treatments For Leishmaniasis: Intrinsic Challenges, Recent Developments and Next Steps - Pacheco-Fernandez T; Markle H; Verma C; Huston R; Gannavaram S; Nakhasi HL; Satoskar AR (Dove Medical Press, 2023)
Thalia Pacheco-Fernandez,1,* Hannah Markle,1,* Chaitenya Verma,2 Ryan Huston,2,3 Sreenivas Gannavaram,1 Hira L Nakhasi,1 Abhay R Satoskar2,3 1Division of Emerging and Transfusion Transmitted Disease, Center for Biologics Evaluation and Research Food and Drug Administration, Silver Spring, MD, 20993, USA; 2Department of Pathology, Wexner Medical Center, The Ohio State University, Columbus, OH, 43201, USA; 3Department of Microbiology, Wexner Medical Center, The Ohio State University, Columbus, OH, 43201, USA*These authors contributed equally to this workCorrespondence: Abhay R Satoskar, Email abhay.satoskar@osumc.eduAbstract: Leishmaniasis is a neglected tropical disease endemic primarily to low- and middle-income countries, for which there has been inadequate development of affordable, safe, and efficacious therapies. Clinical manifestations of leishmaniasis range from self-healing skin lesions to lethal visceral infection with chances of relapse. Although treatments are available, secondary effects limit their use outside the clinic and negatively impact the quality of life of patients in endemic areas. Other non-medicinal treatments, such as thermotherapies, are limited to use in patients with cutaneous leishmaniasis but not with visceral infection. Recent studies shed light to mechanisms through which Leishmania can persist by hiding in cellular safe havens, even after chemotherapies. This review focuses on exploring the cellular niches that Leishmania parasites may be leveraging to persist within the host. Also, the cellular, metabolic, and molecular implications of Leishmania infection and how those could be targeted for therapeutic purposes are discussed. Other therapies, such as those developed against cancer or for manipulation of the ferroptosis pathway, are proposed as possible treatments against leishmaniasis due to their mechanisms of action. In particular, treatments that target hematopoietic stem cells and monocytes, which have recently been found to be necessary components to sustain the infection ...